The Effect of Emotional Intelligence with Work-Life Balance and Burnout on Job Satisfaction - Azzahra Dynaeira Nathaya; Nurdin Hidayat; Sholatia Dalimunthe (Journal of Business and Behavioural Entrepreneurship, 2022)
This study aims to find the effect of Emotional Intelligence with Work-Life Balance and Burnout on Job Satisfaction. The method used is a quantitative method. The sampling technique used purposive sampling which refers to Isaac and Michael's table so that a population of 248 respondents was obtained. The object of research in this study is a teacher at a State Vocational School in DKI Jakarta. Data were collected through a questionnaire using a modified 4-point Likert scale. The results showed that emotional intelligence had a positive effect on job satisfaction, with a t-statistic value > 1.96, which was 8.795. Work-life balance has a positive effect on job satisfaction, with a t-statistic value > 1.96, which is 3,533. Burnout has a negative effect on job satisfaction, with a t-statistical value > 1.96, which is 4.610. Emotional intelligence has a positive effect on work-life balance, with a t-statistic value > 1.96, which is 7.263. Emotional intelligence has a negative effect on Burnout, with a t-statistic value <1.96 which is 7358. Work-life balance mediates the effect of emotional intelligence on job satisfaction, with a t-statistic value > 1.96, which is 4,021. Burnout mediates the effect of emotional intelligence on job satisfaction, with a t-statistic value > 1.96, which is 2.859. There is an influence of 54.7% between the dependent variable, namely emotional intelligence (X), work-life balance (Z1) and Burnout (Z2) on the dependent variable in the form of Job Satisfaction (Y).